Scope, Possibility and Risks in Hydropower Development in the North East Region of India - Jain, Sharad K. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
The North Eastern Region (NER) of India has immense untapped hydropower potential which can be an excellent source of electricity for India. Hydropower development is also expected to trigger overall growth of the region and improve infrastructure. Hydropower potential of NER should be exploited through an optimal mix of runof- river and storage projects. This paper discusses the prospects, possibilities and practical aspects of hydropower development in this region. DOI: http://dx.doi.org/10.3126/hn.v11i0.7156 Hydro Nepal Vol.11 2011 pp.18-24